Effect of Online Learning On Mathematical Critical Thinking Skills of Grade VIII Junior High School Students - Fitri Umardiyah; Abdur Rohman; Eliza Verdianingsih (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This research aims to find out whether or not online learning affects the mathematical critical thinking skills of class VIII. The method used in this study is Pre-Experimental Designs with a quantitative approach, this research design uses a one-group pretest-posttest design. The subject of this study is a class VIII student at Madinatul Ulum Jombang Junior High School in the 2021/2022 school year. The instruments used in this study are tests and non-test. The data collection techniques in this research are test and Questionnaire test, and data analysis using t-test with the help of SPSS application version 16 for windows. The results of online learning on mathematical critical thinking skills obtained a significance value of < 0.05, namely a test significance value of 0.003 < 0.05 and a Questionnaire significance value of 0.000 < 0.05. This shows that there is an influence of online learning on the mathematical critical thinking skills of grade VIII students.